Elasticity of the sacculus of Escherichia coli. - Koch, A L (1992)
Preparations of purified peptidoglycan of Escherichia coli (i.e., sacculi) were studied by low-angle laser light scattering. Control experiments and theoretical calculations based on the Rayleigh-Gans theory showed that the mean sacculus surface area could be accurately inferred from measurements with our apparatus by using computer routines developed previously. Large changes in the mean saccular surface area resulted from alterations in the stress caused by varying the net charge on the sacculi. The net charge was affected by altering the suspending medium pH, causing carboxyl and amino groups in the peptidoglycan to gain or lose protons, or by acetylation or succinylation of the amino groups. A preponderance of either plus or minus charges caused an expansion of the mean sacculus surface area. The largest increase in area probably represents the elastic limit of the peptidoglycan and was 300% above the area of isoionic sacculi. This degree of expansion is consistent with possible conformations of the intact peptidoglycan structure without necessitating rupture of the wall fabric. Our findings concerning saccular elasticity provide support for the surface stress theory. It provides a mechanism so that bacteria can grow and divide while maintaining turgor pressure, without the necessity of having and using proteins to do the mechanical work.